Twentieth-century Suriname : continuities and discontinuities in a new world society - Hoefte, Rosemarijn (Ian Randle Pub. KingstonJM, 2001)
Covers the demography, social structure, economy, politics, foreign relations and major continuities viz. the economic structure, the multiethnic society and the special relationship with the Netherlands.